Long-Term Properties of Cement-Based Composites Incorporating Natural Zeolite as a Feature of Progressive Building Material - Alena Sičáková; Matej Špak; Mária Kozlovská; Marek Kováč (Advances in Materials Science and Engineering)
This study is aimed at the utilization of natural zeolite as a prospective type of Supplementary Cementitious Material in connection with the innovations of construction solutions through the materials. The influence of zeolite on several properties of cement-based composites is studied. Basic characteristics of input powdery materials as well as the technological parameters of zeolite tested on mortar containing 50% of cement replacement are presented. The technical parameters of concrete containing 8, 13, and 25% of cement replacement by zeolite are presented as well. The paper is valuable due to the three-year testing period. The density of the hardened concrete was found to be decreasing with increasing zeolite content. While no significant differences in compressive strength were found after 28 days, differences between individual samples were clear after the long-term period. The presence of zeolite influenced the compressive strength positively in the case of the 8% and 13% replacement, while the higher proportion of natural zeolite (25%) caused lower compressive strength after 28 days but was similar to the reference concrete after three years. A major increase in strength was detected for all samples in the long-term period. It confirms the long-term potential of zeolite for strength improvement.